Circadian Blood Pressure Profile and Associated Cardiovascular Risk Factors in Non-Dippers - MY, Siti Suhaila; S, Juwita; MY, Harmy; T, Tengku Alina (IIUM Medical Journal Malaysia, 2013)
Introduction: Ambulatory blood pressure accurately reflects a patient's actual blood pressure than casual or office blood pressure. This study aims to describe the circadian blood pressure profile of hypertensive patients and to identify the associated cardiovascular risk factors in non-dippers. Methods: A cross-sectional study was conducted from 1st January 2008 to 30th June 2008 among hypertensive patients attending Family Medicine Clinic HUSM. Schiller BR-102 plus was used to get 24 hours blood pressure (BP) reading. Mean of two offices BP were also taken. Non-dippers are defined as a systolic or diastolic nocturnal drop of less than 10%. Analysis was done using SPSS Version 12. Results: 105 patients were recruited with mean (SD) age of 51.8 (9.34) year old. The mean (SD) 24-hour systolic and diastolic BP was 128.4 (12.7) mmHg and 79.7 (8.74) mmHg respectively. Mean (SD) daytime systolic and diastolic BP was 132.1 (11.72) mmHg and 82.4 (9.41) mmHg while for the night time were 123.3 (12.78) mmHg and 76.2 (9.01) mmHg. Mean (SD) systolic and diastolic office BP was 144.2(15.16) mmHg and 90.2(9.71) mmHg. Percentage of non dippers were 68.6% for systolic and 61.9% for diastolic. Conclusion: Mean 24 hours and daytime ambulatory BP was normal but the mean night time diastolic and office BP was above-normal value. Majority of the patients were categorized as non dippers. Therefore, using ambulatory BP is clinically important to get a better understanding of blood pressure fluctuations over 24-hour periods compared to simple clinical measurements.